Ticks (Acari: Ixodidae) on Wild Marsh-Deer (Blastocerus dichotomus) from Southeast Brazil: Infestations before and after Habitat Loss - Szabó, Matias P. J.; Labruna, Marcelo B.; Pereira, Marcelo C.; Duarte, José Maurício B. [UNESP] (My University, 2003)
The lake from Porto-Primavera hydroelectric power station inundated an area of 2,200 km2 at the border of São Paulo and Mato-Grosso do Sul States, Brazil. Infestations by ticks were evaluated on 135 marsh deer, Blastocerus dichotomus (Illiger), captured before and after inundation. Ticks were collected for identification, and infestation level of animals was assessed by scoring. Deer were divided into four groups according to capture location and temporal relation to the inundation. Groups 1, 2, and 3 were captured before inundation. Group 4 was captured after inundation. Four tick species were found: Amblyomma cajennense (F.), Amblyomma triste Koch, Anocentor nitens (Neumann), and Boophilus microplus (Canestrini). Groups 1, 2, 3, and 4 had 30, 45, 100, and 96%, respectively, of animals carrying B. microplus ticks. A. triste was observed on 16, 22, 22, and 88% of animals from groups 1,2,3, and 4, respectively. A. nitens and A. cajennense were observed only on group 4, on 32 and 16% of the animals, respectively. Groups 1 and 2 had only 4.8 and 6.1% of animals with high infestation levels, respectively, and no ticks on 46.8% and 45.5% of the animals, respectively. Conversely, groups 3 and 4 lacked noninfested animals and had high infestation levels on 77.8 and 50% of deer, respectively. Marsh area shrinkage was blamed for higher infestation levels on deer from groups 3 and 4. The widespread presence of A. triste on marsh deer, a Neotropical tick species, raises the possibility of a natural host-parasite relationship.
Keywords: Amblyomma cajennense; Amblyomma triste; Anocentor nitens; Blastocerus dichotomus; Boophilus microplus; Marsh deer; Acari; Animalia; Caesalpinia ciliata; Cervidae; Ixodidae; Tabebuia donnell-smithii; animal; animal disease; Brazil; deer; environment; geography; infestation; parasitology; tick; Animals; Deer; Environment; Geography; Tick Infestations